Molecular characterization of two isoforms of defensin from hemocytes of the oyster Crassostrea gigas - Gonzalez, Marcelo; Gueguen, Yannick; Desserre, Geraldine; De Lorgeril, Julien; Romestand, Bernard; Bachere, Evelyne (Developmental & Comparative Immunology, 2007)
Antimicrobial peptides (AMPs) are important components of the host innate immune response against microbial invasion. We previously characterized the first AMP from an oyster, a defensin, that was shown to be continuously expressed in the mantle of Crassostrea gigas. In this study, we report the cDNA cloning of two new isoforms of the defensin AMP family (Cg-defh1 and Cg-defh2) from the hemocytes of the oyster. The deduced amino acid sequences reveal two peptides of 73 amino acid residues with a mature portion consisting of 43 amino acid residues. Cy-Defh1 and CyDefh2 share 86% amino acid identity and belong to the "arthropod-molluscs defensin family". qRT-PCR analyses indicate that Cg-defh2 is continuously expressed in the hemocytes of C. gigas. In addition, after a bacterial challenge, the level of Cg-defh2 transcripts decreases dramatically in the circulating hemocyte population and this decrease can be correlated with an increase of Cg-defh2 transcripts in the gill and the mantle tissue, suggesting a possible migration of the hemocytes expressing Cg-defh2 towards the tissues implicated in the first defense barrier of the oyster. These results would suggest an important role of Cg-Defh2 in the oyster response to a microbial challenge. (c) 2006 Elsevier Ltd. All rights reserved.